Carcass tissue distribution and characteristics of Small East African and Galla goats, and their F1 crosses to Toggenburg and Anglo-Nubian - OKEYO, A M; WANYOIKE, M M; AHUYA, C O (The Indian Journal of Animal Sciences, 2014)
Pre-slaughter live weights (LW) and carcass characteristics (hot and cold dressed weights (CDW), total lean (TL), total bone (TB), total fat (TF), and fat components such as intestinal fat, subcutaneous fat, empty gut (EG) and other offal weights were determined in 60 females, male and castrated goats of SEA and Galla and their respective F, crosses with Toggenburg and Anglo-Nubian of approximately 3 years of age. Breed group, sex and their first order interactions were tested for relative influence on some of the carcass characteristics. Sex of the animal did not significantly affect the carcass chilling shrinkage (%). However, sex significantly (P<0.001) influenced the weights of offal such as head, skin and empty gut as proportions of the live weight. The shrinkage (%) ranged between 2.87 and 2.66 with male carcasses shrinking most followed by castrates and females. Estimates of proportions of skin and EG to LW were: 5.45.5.51. 6.32 and 8.07, 5.57 and 7.48 for castrates, females, respectively, and for skin and EG in that order. Shrinkage (%) was higher among Toggenburg crosses (3.3%; 2.9%) and lowest among the SEA (2.3%), while Galla and Anglo-Nubian crosses registered intermediate values (2.62 and 2.66%).